Genetic association of SLC2A9 variants with gout susceptibility in Malay population - Adanan @ Adnan, Mahfudzah (2015)
Gout is an inflammatory arthritis that is caused by the formation of multiple needles like uric acid crystals in joints. It occurs when serum uric acid (SUA) levels rise and the physiological saturation is exceeded in body fluids. Renal urate excretion is controlled by the SLC2A9 gene which acts as a renal urate transporter and involves in the developing of tophaceous gout. Therefore the main objective of this study is to test genetic association of four common variants of SLC2A9 gene and demographic features of gout in Malay population. Blood samples were taken from 3ml whole blood according to Qiagen Extraction Kit and genotyping was conducted utilizing polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method for 4 SNPs namely rs5028843, rs3733591, rs11942223 and rs16890979. The average Minor Allele Frequency (MAF) of 0.018 with OR of 4.374 requires 89 samples of cases that project 80% power of study. Hardy Weinberg equilibirium was calculated by using SHEsis online software providing odd ratios and 95% confidence interval. Our data confirmed the role of the SLC2A9 gene of susceptibility of gout in the Malay descendents in Malaysian population which was seen by the effect ofsusceptible risk of (OR>2.0). Our study showed that the minor allele of rs3733591, rs1194223 and rs5028843 have influenced on the activity of SLC2A9 in articular chondrocytes increases the risk for deposition of MSU crystals and tophi formation. In summary, the association of 1/2/1/1, 1/1/2/1 and 1/1/1/2 haplotypes confer haplotypes which reflects the increase of gout development.